Gender Perspektif Teori feminisme, Teori Konflik dan Teori Sosiologi - Nurjannah Nurjannah (AL-WARDAH: Jurnal Kajian Perempuan, Gender dan Agama, 2022)
Gender is an analysis used in placing equal positions between men and women to create a more egalitarian social order. So, gender can be categorized as an operational tool in measuring (measures) the problems of men and women, especially those related to the division of roles in society that is constructed by the community itself. Gender is not only addressed to women, but also to men. However, it is women who are considered to be experiencing a marginalized position now, so it is women who are more prominent in the discussion to pursue gender equality which has been achieved by men at several levels in social roles, especially in the field of education because this field is expected to encourage changes in the framework of thinking. , act, and play a role in various segments of social life.